A single serum glucose measurement predicts adverse outcomes across the whole range of acute coronary syndromes. Issue 5 (1st May 2003) - Foo, K; Cooper, J; Deaner, A; Knight, C; Suliman, A; Ranjadayalan, K; Timmis, A D
Abstract : Objectives: To analyse the relation between serum glucose concentration and hospital outcome across the whole spectrum of acute coronary syndromes. Methods: This was a prospective cohort study of 2127 patients presenting with acute coronary syndromes. The patients were stratified into quartile groups (Q1 to Q4) defined by serum glucose concentrations of 5.8, 7.2, and 10.0 mmol/l. The relation between quartile group and major in-hospital complications was analysed. Results: The proportion of patients with acute myocardial infarction increased incrementally across the quartile groups, from 21.4% in Q1 to 47.9% in Q4 (p < 0.0001). The trend for frequency of in-hospital major complications was similar, particularly left ventricular failure (LVF) (Q1 6.4%, Q4 25.2%, p < 0.0001) and cardiac death (Q1 0.7%, Q4 6.1%, p < 0.0001). The relations were linear, each glucose quartile increment being associated with an odds ratio of 1.46 (95% confidence interval (CI) 1.27 to 1.70) for LVF and 1.52 (95% CI 1.17 to 1.97) for cardiac death. Although complication rates were higher for a discharge diagnosis of acute myocardial infarction than for unstable angina, there was no evidence that the effects of serum glucose concentration were different for the two groups, there being no significant interaction with discharge diagnosis in the associations between glucose quartile and LVF (p = 0.69) or cardiac death (p = 0.17). Similarly there was no significant interaction with diabetic status in the associations between glucose quartile and LVF (p = 0.08) or cardiac death (p = 0.09). Conclusion: Admission glycaemia stratified patients with acute coronary syndromes according to their risk of in-hospital LVF and cardiac mortality. There was no detectable glycaemic threshold for these adverse effects. The prognostic correlates of admission glycaemia were unaffected by diabetic status and did not differ significantly between patients with acute myocardial infarction and those with unstable angina.